Neural development and plasticity - Mize, R. Ranney; Erzurumlu, Reha S. (Progress in brain research, 1996)
This Progress in Brain Research volume is the outgrowth of a symposium entitled "Neural Development and Plasticity" which was held in New Orleans, Louisiana. The reader will find substantial new information about the mechanisms underlying growth cone dynamics, about molecules involved in axon outgrowth and cell adhesion, the role of proteoglycans and glial factors in directing or confirming axons to their appropriate targets, and the role of myelin-associated growth inhibitors. The book will contribute new ideas and identifies new questions of primary importance to developmental neurobiology.